Subnational Income Growth and International Border Effects - Hanna L. Adam; Mario Larch; David Stadelmann (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper analyses the effect of international borders and of trade agreements at international borders on subnational (i.e. regional) growth. We construct an extensive panel dataset covering 1,350 regions in 86 countries worldwide between 1950 and 2017. Our results show that international borders decrease regional income per capita, while trade agreements at international borders increase regional income per capita by about the same magnitude. The positive marginal effect of trade agreements on regional income corresponds to at least three fifths of the negative marginal effect of international borders. Thus, trade agreements can compensate negative border effects and explain regional inequalities within countries. An array of robustness tests supports our interpretations.
Keywords: F14; F15; F43; O18; R12; 330; border effects; trade; trade agreements; GDP per capita; regional analysis